Wymiana informacji między przedsiębiorcami w świetle reguł konkurencji UE - Kostecka-Jurczyk, Daria (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Information exchange agreements are one of the core problems of EU competition policy. On the one hand they are one of a tool of cooperation and can increase capacity of enterprises as well as quality of goods and services. This means that one of the beneficents of this agreements can be consumer. However in most cases EU competition authority proves that exchange of information is harmful for markets and for competition. In practice its hard to take effective means to prevent anticompetitive exchange of information because its hard to prove disruption of competition. The aim of that article is to show the way of evaluation such as agreements and to answer the question in what cases exchange of information between entrepreneur distort effective competition and infringe the Article of 101 Lisbon Treaty
Keywords: exchange of information; agreement to exchange of information; horizontal agreements; cartels